The use of antiepileptic medication in early post traumatic seizure prophylaxis at a single institution. (November 2019) - Candy, Nicholas; Tsimiklis, Chrisovalantis; Poonnoose, Santosh; Trivedi, Riki
Highlights: In clinical practice antiepileptic medications other than phenytoin are prescribed for post traumatic seizure prophylaxis. This was a retrospective case not review of all traumatic intracranial haematomas that presented to a single institution over a 4 year period. 16% of patients were prescribed an antiepileptic drug. Rate of early PTSs for patients prescribed antiepileptic drugs was 2.9% compared with 3.5% for patients not prescribed antiepileptic drugs. The routine administration of prophylactic antiepileptic medications that occurs in clinical practice should be re-examined. Abstract: Background: Current international guidelines for traumatic brain injury (TBI) recommend the use of phenytoin for the prevention of early post traumatic seizures (PTS) when the benefits are thought to outweigh the risks. In practice however, alternative antiepileptic drugs (AEDs) such as levetiracetam and valproate are being used as they are believed to have a more favourable risk profile. This is despite there being insufficient evidence to support their efficacy. The purpose of this study was to identify which AED was prescribed to patients presenting with a TBI at a single institution, and to determine the rate of early PTSs. Methods: This was a retrospective case-note review study done at the Flinders Medical Centre including patients admitted from May 2013 to June 2017. All patients with traumatic intracranial haematomas were included. Patients were excluded if they had seizures prior to presentation to hospital or died within 24 h of injury. The primary outcomes were rate of early PTSs and the type of prophylactic AED prescribed. Results: During this study period, 610 patients presented with a mild, moderate or severe traumatic brain injury. Overall, 16% of patients were prescribed an AED, with more than 90% of these patients being prescribed levetiracetam. Overall, the rate of early PTSs for patients prescribed AEDs was 2.9% compared with 3.5% for patients not prescribed AEDs (OR 0.83 CI 0.24–2.85 p = 1). Conclusions: This study showed that levetiracetam was the most commonly prescribed AED. It also demonstrated no statistically significant difference in the rate of early PTSs in patients with TBI, with or without prophylactic AEDs. This is in keeping with other contemporary studies, and therefore the routine administration of prophylactic AEDs may need to be re-examined.